A Crowding-out Effect for Relative Income - Benno Torgler; Bruno S. Frey; Markus Schaffner; Sascha L. Schmidt (Center for Research in Economics, Management and the Arts (CREMA), 2008)
The risk of external interventions crowding-out intrinsic motivation has long been established in economics. This paper introduces a new dimension by arguing that a crowding-out effect does become possible if individuals receive higher relative compensation. Using a unique, large data set that focuses on 26 seasons in basketball (NBA) we find empirical support for a relative crowding-out effect. Performance is reduced as a reaction to a relative income advantage.
Keywords: D00; D60; L83; 330; Crowding-out; relative income; positional concerns; motivation